Atenolol increases dental mineralization in male offspring of treated hypertensive rats and normotensive rats - Elias, Gracieli Prado (2020)
This study evaluates how atenolol affects dental mineralization in offspring of female spontaneously hypertensive rats (fSHR) and normotensive Wistar rats (fW). fSHR and fW were treated with atenolol (100 mg/Kg/day, orally) during pregnancy and lactation. Non-treated fSHR and fW were the control groups. Enamel and dentin hardness were analyzed (Knoop, 15 g load, 10s) in mandibular incisor teeth (IT) and molar teeth (MT) obtained from the male offspring of atenolol-treated and non-treated fWistar and fSHR. Data were analyzed by ANOVA, followed by Tukey post hoc test (p < 0.05). Atenolol reduced the arterial blood pressure (SBP) in fSHR, but it did not change the SBP in fW. The offspring of non-treated fSHR had lower enamel (IT and MT) and dentin (IT) hardness than the offspring of non-treated fW (p < 0.05). Atenolol increased enamel and dentin hardness in the IT obtained from the offspring of fSHR and fW (p<0.05), but the offspring of fSHR presented higher values (p < 0.05). Atenolol did not alter enamel width in the IT obtained from any of the groups, but it increased enamel and dentin hardness in the IT obtained from the offspring of fSHR and fW. Atenolol affected the IT obtained from the offspring of fSHR. Atenolol increased only enamel hardness in the MT obtained from the offspring of fW. In conclusion, maternal hypertension reduces tooth hard tissues, and treatment with atenolol increases tooth hardness in male offspring of hypertensive and normotensive female rats.